Folic acid deficiency damages male reproduction via endoplasmic reticulum stress-associated PERK pathway induced by Caveolin-1 in mice. (3rd September 2021) - Zhang, Yuan; Yuan, Hongfang; Peng, Meilin; Hu, Zhiyong; Fan, Zunpan; Xu, Jia; He, Liting; Wang, Yongfeng; Wang, Wei; Su, Yufang; Liu, Chunyan; Zhang, Huiping; et al.
ABSTRACT: Folic acid is critical to maintaining normal male reproductive function. Endoplasmic reticulum (ER) stress plays a crucial role in folic acid deficiency. Studies have shown that Caveolin-1 (Cav-1) is involved in ER stress, but the specific mechanism in male reproduction is still unclear. This study aimed to investigate the effects of folic acid deficiency on spermatogenesis and elucidate the underlying mechanisms. C57BL/6 mice fed with folic acid deficiency induced diet(0.3 mg/kg) were used. A significant decrease in the sperm concentration in the folic acid deficiency group was observed. Meanwhile, folic acid deficiency decreased Cav-1 expression in the testis tissue and increased endoplasmic reticulum stress-related PERK, eIF2α, ATF4, CHOP gene expression. Our results suggest that folic acid deficiency can affect male reproduction through the Cav-1-PERK-eIFα-ATF4-CHOP pathway. Abbreviations : ATF4: activating transcription factor 4; Ca2+: calcium ion; Cav-1: Caveolin-1; CCK-8: cell counting kit-8; CHOP: CCAAT-enhancer-binding protein homologous protein; DNA: Deoxyribonucleic acid; DSB: double strand breakage; eIF2α: eukaryotic Initiation Factor 2 alpha; ER: endoplasmic reticulum; FD: folic acid deficiency; FITC: fluorescein isothiocyanate; HE: hematoxylin and eosin; H3K4me3: histone H3 lysine 4 trimethylation; PERK: protein kinase RNA-like endoplasmic reticulum kinase; PI: propidium iodide; RT-qPCR: quantitative reverse transcription PCR; TUNEL: TdT mediated dUTP Nick End Labeling